A novel approach to iron oxide separation from e-waste and bisphenol A detection in thermal paper receipts using recovered nanocomposites. Issue 70 (29th November 2018) - Akilarasan, Muthumariappan; Kogularasu, Sakthivel; Chen, Shen-Ming; Chen, Tse-Wei; Lou, Bih-Show
Abstract : To promote sustainability, the effective reutilization of electronic waste and profitable recovery of valuable materials from e-scrap are essential. Abstract : To promote sustainability, the effective reutilization of electronic waste and profitable recovery of valuable materials from e-scrap are essential. A recent report showed that 500 million printer cartridges enter landfill annually, creating immense interest in establishing a facile recovery method for transforming waste toner into a ferrous resource. Furthermore, the European Union and US Food and Drug Administration have published guidelines concerning bisphenol A (BPA) use in the manufacture of thermal paper receipts. Accordingly, in this study, BPA levels in thermal receipts collected from various stores in Taiwan were detected by glassy carbon electrodes fabricated using graphene oxide-recovered Fe3 O4 nanocomposites.